Surface Modification of 3D Printed PLA Objects by Fused Deposition Modeling: A Review - Eda Hazal Baran (Colloids and Interfaces, 2019)
Polylactic acid (PLA) filaments are very popular as a thermoplastic source used in the 3D printing field by the “Fused Deposition Modeling„ method in the last decade. The PLA market is expected to reach 5.2 billion US dollars in 2020 for all of its industrial uses. On the other hand, 3D printing is an expanding technology that has a large economic potential in many industries where PLA is one of the main choices as the source polymer due to its ease of printing, environmentally friendly nature, glossiness and multicolor appearance properties. In this review, we first reported the chemical structure, production methods, general properties, and present market of the PLA. Then, the chemical modification possibilities of PLA and its use in 3D printers, present drawbacks, and the surface modification methods of PLA polymers in many different fields were discussed. Specifically, the 3D printing method where the PLA filaments are used in the extrusion-based 3D printing technologies is reviewed in this article. Many methods have been proposed for the permanent surface modifications of the PLA where covalent attachments were formed such as alkaline surface hydrolysis, atom transfer polymerization, photografting by UV light, plasma treatment, and chemical reactions after plasma treatment. Some of these methods can be applied for surface modifications of PLA objects obtained by 3D printing for better performance in biomedical uses and other fields. Some recent publications reporting the surface modification of 3D printed PLA objects were also discussed.